Insurgency and Extreme Poverty: Evidence from the Boko Haram Crisis in Northeast Nigeria - Emmanuel Elomien; Victor Jubril; Olumuyiwa Ajayi; Sheriff Folarin (Covenant University Journal of Politics and International Affairs, 2023)
Since the return to civilian rule in Nigeria in 1999, successive political administrations have sought to create wealth and prosperity for the people as one of the dividends to be expected from a democratic government to her citizens. However, such measures have not yielded much results as expected, as poverty continues to be on the increase. This unexpected situation has thus elicited interests amongst social, economic and political researchers and analysts who seek to understand the dynamics and consequences of the trajectory. This trend is met with a concomitant increase in crime and militancy, particularly the rise and expansion of Boko Haram’s blood-cuddling activities in the Northeast. This chapter therefore, examines the activities of the Boko Haram insurgent group with a view to determining whether their activities have a significant impact on the poverty curve in Nigeria. The paper relies on secondary data collection methodology to arrive at the presented findings on the nexus between insurgency in Northeastern Nigeria and the growing extreme form of poverty. The chapter recommends that political and socio-economic approaches and putting in place a sustainable development programme will reduce the potency of Boko Haram activities and de-escalate poverty in the region. .